DEVELOPMENT OF AKHLAQ WITH THE MCCB MODEL: STRENGTHENING TEACHER LITERATURE - Lalu Asriadi; Ziyad (Ite Ngabdi, 2025)
This study strengthens teacher literature on efforts to overcome bullying in Madrasah. Bullying is a matter that can be a stumbling block for schools in presenting humanity. Teachers need supplementary knowledge on fostering students’ morals with the MMCB model. The results of the community service provide an overview that teachers increasingly understand the MMCB model and how to anticipate and handle it. Teachers also seem enthusiastic about the material. The first material is about bullying behavior at school, which includes understanding the forms, causes, and how to overcome bullying attitudes. The second material is about Moral Development, which consists of understanding morals, types of morals, how to strengthen morals, and the role of teachers and parents in fostering children’s morals